Examining the Stages of Relationships Through a Theatrical Lens - Strothenke, Dana; Grothe, Arthur (My University, 2017)
In modern theatre, we have found evidence of all stages of relationships except for the last, true love stage called “Agape Love.” The lack of representation of this stage in our media may be both a cause and effect for our increasing divorce rate and lack of satisfaction among couples today.
Color poster with text.
Keywords: Theater; Romance; Agape love; Relationships; Posters